Formulating academic word lists of English reading tests for Indonesian undergraduate students - Homsatun Nafiah; Gusti Ayu Praminatih (ELT Forum: Journal of English Language Teaching, 2025)
The present study aims to bridge the gaps in the scarcity of academic word lists by constructing specialised English reading test word lists and their significance in enhancing English as a Foreign Language students’ abilities. In reading, students usually experience problems with so much vocabulary available. The International English Language Testing System (IELTS) with 32.819-word tokens was selected using AntFileConverter to formulate the academic word list. Subsequently, AntWordProfiler was utilised to compare the data with 250 words inside General Word List 1, 250 words outside General Word List 2 and the overall words outside Coxhead’s Academic Word List. The 500 highest-frequency words established the Academic Word List for the English reading test. The constructed word list was formulated using several tools, i.e. Familizer+Lemmatizer, Cambridge Dictionary, Sketch Engine, and AntConc. To evaluate the significance of the word list, thirty students from second and third-year Indonesian undergraduate students majoring in English literature were segregated into control with regular materials and experimental groups with the specialised materials and taught using Graves’ vocabulary principles for fourteen meetings in one academic semester. Eventually, the finding demonstrates that word list significantly affects Indonesian students’ reading performance. It confirms that the formulated word list is suitable to be implemented for English reading test purposes. The score results show that students from the control and the experimental groups both improved, whereas the improvement in the experimental group is more significant. This suggests the need for academic word lists for students in the reading test.